Computing Essentials : Making IT work for you - O'Leary, Timothy J., 1947-; O'Leary, Linda I.; O'Leary, Daniel A., (Electrical engineer) (New York, NY : McGraw-Hill Education, 2015)
How are you learning about the most important, essential, and current concepts of information technology? This title allows you to Make IT Work for You through relevant explorations, ethics and environment sections throughout each chapter.
Include index
Keywords: Computers; Electronic data processing